Changes in chemical composition and biological activities of fresh old tea leaves during storage - Dat, Nguye Tien; Phuong Quynh, Le Thi (Vietnam Journal of Chemistry, 2015)
Old tea leaves are a rich source of bioactive polyphenols. However unsuitable storage could cause the decrease in quality of this material. This work evaluated the change in EGCG, total polyphenol contents as well as the antioxidant, a-glucosidase and a-amylase inhibitory activities of the fresh old tea leave during 48 h under different storage conditions. The fresh old tea leaves were stored under 4 oC or at room condition. Total phenolic content, EGCG and caffeine in the tea leave extracts were quantified by HPLC analysis. a-glucosidase and a-amylase inhibitory activities of the extracted were evaluated by enzyme assays. The results showed that the EGCG, and total polyphenol contents in old tea leaves rapidly decreased after 48 h under room temperature condition while the sample storage at 4 oC retarded their decrease. The biological activity test showed that the inhibition of a-glucosidase and a-amylase decrease proportionally with the changes in EGCG, and total polyphenol contents. In contrast, the antioxidant of the old tea leaves during 48 h storage expressed by the DPPH scavenging capacity slightly augmented due to unknown mechanism. The storage of old tea leaves at room temperature caused the decomposition of EGCG and other polyphenols, which affected the quality of this material regarding its biological properties. The storage at 4 °C significantly protected samples from chemical decomposition and therefore conserved their quality